(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
Mature and planning development is one of the important aspects which is also a benchmark for the progress of a country through village development planning is the initial step to determine the goals for village progress and independence. This study aims to determine the development planning in petta village east tabukan subdistrict north of sangihe island regency. The method used in this research is a descriptive qualitative method with the inductive approach. Qualitative descriptive research with an inductive approach is a method that illustrates the problem or case that is based on the facts that are based on specific facts and then examined to solve the problem and draw conclusions generally. Researchers used five indicators namely determining goals, develop the premise (opinion), determine alternative-alternative actions and evaluate this alternative, choose one of the best alternatives, implement a plan and evaluate the results. Based on the results of research conducted that village development planning has not fully gone well. This is seen in physical development (community needs) and non-physical development as a whole has not gone well, yet there are still many community needs that have not been met. Keywords : Planning, Development, Village.